Community participation: towards a safer housing environment / Hafazah Abdul Karim and Siti Mareenah Abdul Rashid - Abdul Karim, Hafazah; Abdul Rashid, Siti Mareenah (Universiti Teknologi MARA Cawangan Selangor, 2017)
Lately crime rate in Malaysia has increased thus threatening the safety and security of the community especially those in high density areas. There are crimes that had targeted women and children and this had caused much stress to the urban residents. Human responses to these issues are to band together and take control of their environment and this is what happened to the residents in the PKNS flats in Taman Dato’ Harun, Petaling Jaya. They wanted to build a close knit community that involve in community activities and at that same time this community will take care of each other’s safety. This paper revolves around the participation of the residents in the PKNS flats in Taman Dato’ Harun in Rukun Tetangga (RT) with the purpose to increase community involvement and interaction which will eventually lead to a more caring community. These flats have won the Petaling Jaya City Council Best Neighbourhood Contest in 2006 for its community activities. They consist of 300 housing units in five blocks of five storey flats. A sample of 30 percent (90 units) was taken by a stratified random sampling where every block and every level were accounted for. The data acquired was analysed using the SPSS programme. Findings showed that 100 percent of the respondents know their neighbours, 99 percent cooperate in community activities, 83 percent actively participated in RT, 85 percent of the respondent felt safe living in their flats, 72 percent felt that RT helped prevent crime and social misconduct. Other findings also showed that the community are very satisfied with the existence of the RT and felt that the activities have helped to foster positive community relations. This in turn decreases the perception of fear living in the urban area and instead gave the residents the perception of safety and well-being.